Worker Protection Standard: Employer Information Exchange - Frederick M. Fishel (EDIS)
Employers of commercial pesticide handlers must make sure that their customers – the operators of farms, forests, nurseries, or greenhouses – know certain information about the pesticides to be applied on their establishments. At the same time, the customers (agricultural employers) must give the commercial handler's employer specific information concerning treated areas. This document is PI-115, one of a series of the Pesticide Information Office, UF/IFAS Extension. Original publication date April 2006.